Distance decay is uncommon in large‐scale population synchrony of common moths: does it promote vulnerability to climate change?. Issue 5 (6th March 2015) - Nieminen, Marko; Dytham, Calvin; De Vries, Phil
Abstract Large‐scale spatial synchrony is common in population dynamics. In nearly all empirical data sets, population synchrony decays with distance. Large‐scale spatial population synchrony of 20 common moth species was studied using 367 separate light‐trap time series of 3–27 years, at 13–19 localities in southern Finland. The maximum distance between trap sites was ca 1075 km. The degree of spatial synchrony in three weather variables (daily mean and minimum temperature, and daily total precipitation) from 15 weather stations was also studied. Data were analysed with spatial non‐parametric correlation functions (Sncf). Statistically significant large‐scale spatial synchrony in population fluctuations occurred in 85% of the species (Scotopteryx chenopodiata, Eulithis populata, Chloroclysta citrata, Epirrita autumnata, Perizoma alchemillata, P. didymata, Eupithecia pusillata, Macaria wauaria, Itame brunneata, Cabera pusaria, C. exanthemata, Eilema lurideola, Rusina ferruginea, Amphipoea fucosa, Orthosia gothica, Cerapteryx graminis and Diarsia mendica), as well as in all weather variables. Spatial synchrony decreased with distance (=distance decay) in 45% of the species, and there was no indication of distance decay in the remaining species. Climate change is likely to cause an increasing frequency of extreme weather events, and insects are strongly affected by such environmental stochasticity. In combination with the high frequency of large‐scale spatial synchrony, which did not show distance decay as a rule in these data, even currently common moth species may become threatened in the near future.